2018
DOI: 10.1111/odi.12842
|View full text |Cite
|
Sign up to set email alerts
|

Preventive dental management of osteonecrosis of the jaws related to zoledronic acid treatment

Abstract: BRONJ occurred significantly in patients who underwent dental extractions after the initiation of ZA and did not accomplish a preventive dental program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
1
7
1
1
Order By: Relevance
“…The results therefore suggest that nonrestorable teeth and those with poor prognosis should be extracted before the development of inflammation and should not be postponed in cancer patients receiving high‐dose BP and DS. The observations differ from the results reported by Coello‐Suanzes et al (2018), who could not describe connections between MRONJ and periodontal infection. However, in a Swedish prospective study with a 4‐year follow‐up, Hallmer et al (2018) indicated that pre‐existing inflammatory dental disease such as periodontal disease or periapical pathology is a well‐recognized risk factor, assessed as the initiating factor for the development of MRONJ in 18% and 4% of the cases, respectively.…”
Section: Discussioncontrasting
confidence: 99%
“…The results therefore suggest that nonrestorable teeth and those with poor prognosis should be extracted before the development of inflammation and should not be postponed in cancer patients receiving high‐dose BP and DS. The observations differ from the results reported by Coello‐Suanzes et al (2018), who could not describe connections between MRONJ and periodontal infection. However, in a Swedish prospective study with a 4‐year follow‐up, Hallmer et al (2018) indicated that pre‐existing inflammatory dental disease such as periodontal disease or periapical pathology is a well‐recognized risk factor, assessed as the initiating factor for the development of MRONJ in 18% and 4% of the cases, respectively.…”
Section: Discussioncontrasting
confidence: 99%
“…Bifosfonatlar ise osteoporoz, malign tümörlerin osteolitik kemik metastazları, malign tümörlerin neden olduğu hiperkalsemi ve Paget's hastalığı varlığında kullanılırlar (4,5,6,7,8). Bu grup ilaçlar ise kemik osteoklastik aktivitesini ve kemik döngüsünü baskılayarak etki gösterirler (9). Her iki grup ilacın faydalarının yanında, çene kemiklerinde osteonekroza neden olmak gibi kötü bir yan etkileri de vardır.…”
Section: Bifosfonat Kullanımına Bağlı çEne Kemiklerinde Görülen Osteounclassified
“…Studies in animal models have reported that ZA suppresses bone remodelling and increases peri‐implant bone loss, which results in dental implant failures and the development of BRONJ lesions (Davison et al., 2020; Kniha et al., 2020). Furthermore, in most clinical cases, BRONJ can be triggered by the oral wounds during the surgical procedures, such as tooth extractions, periodontal disease and pressure denture sores (Coello‐Suanzes et al., 2018; Walter et al., 2007). As BRONJ cases in relation to dental implant were frequently reported (Bedogni et al., 2010; Fliefel et al., 2015; Kasai et al., 2009; Starck & Epker, 1995), more and more researchers proposed that dental implant therapy could be an risk factor for BRONJ (Kuroshima et al., 2019; Kwon et al., 2014; Mendes et al., 2019; Schmitt et al., 2018).…”
Section: Introductionmentioning
confidence: 99%